Laparoscopic modified subtotal cholecystectomy is a safe method in the management of mirizzi syndrome type I - Kayapinar, Ali Kemal; Sahin, Hilal (Annals of Medical Research, 2022)
Aim: Efforts to reveal the cystic duct and the cystic artery during standard cholecystectomy in Mirizzi Syndrome (MS) without preoperative or intraoperative diagnosis increase the risk of biliary and vascular injury due to intense fibrosis in the Calot’s triangle. We aim to evaluate the postoperative results of a group of MS type I patients who were diagnosed by video scope intraoperatively and underwent laparoscopic modified subtotal cholecystectomy (LMSC) in the same session since safe dissection of Calot’s triangle could not be performed. Methods: Ten out of 1680 patients who underwent conventional laparoscopic cholecystectomy for acute or chronic cholecystitis between 2017 and 2019 were diagnosed with MS type I intraoperatively. These 10 patients underwent LMSC and their demographic characteristics, preoperative clinical histories, radiological images, intraoperative and postoperative findings were evaluated retrospectively. Intraoperative MS type determination and LMSC technique are explained. Results: The diagnoses of MS type I in all our cases were made laparoscopically with the help of a videoscope during the operation where safe dissection of the Calot’s triangle could not be performed in either elective or emergency cholecystectomy. LMSC was performed without leaving any cavity behind, and there was no need for any intervention at the operation site (suture, staple closure) since the cystic duct orifice was already obstructed due to fibrosis as visually verified by the camera. There were no intraoperative bile duct injuries or postoperative biliary fistula. None of our patients developed postcholecystectomy syndrome (range 1-38 months) Conclusion: The LMSC is a safe procedure in the diagnosis and surgery of MS type I where safe dissection of Calot’s triangle could not be performed